Policy report on FinTech data gaps - José Manuel Marqués; Fernando Avila Embriz; Anahí Rodríguez-Martínez; Raúl Morales; Antonio Marcos; Tamara Godoy; Pablo Villalobos; Andrea Ocontrillo; Valerie Ann Lankester; Clemente Alfredo Blanco Velásquez; Karla Reyes; Silvia Irina Lopez; et al. (Latin American Journal of Central Banking (LAJCB), 2021)
This document aims to provide an overview of the main issues related to data gaps to facilitate monitoring of FinTech and overcome the significant challenges towards incorporating FinTech activities in regular statistics. Moreover, the document explains the implications of data gaps on some of the Central Banks' main areas, in particular, monetary policy, financial stability, payment systems, and economic activity. Additionally, other implications related to the activity of BigTech companies, the impact of COVID-19 and Cybersecurity issues are explained, which represent an important challenge for data gathering at Central Banks. Also, it describes the main findings of the Irving Fisher Committee (IFC) survey "Central Banks and FinTech data" based on the answers provided by Latin American and Caribbean (LAC) countries, which identify their different positions regarding this topic and the current initiatives that each one is launching. Finally, a number of next steps are proposed based on a policy discussion and how LAC countries could overcome data gaps and improve data collection based on their current experience.
Keywords: 330